Pollen morphology of the genus Hyacinthella (Asparagaceae) and Muscari azureum in Türkiye - Acar Şahi̇n, Aydan; Eroğlu, Hüseyi̇n (Phytotaxa, 2022)
Pollen morphology of 11 taxa belonging to genus Hyacinthella and also Muscari azureum were examined by light microscopy and scanning electron microscopy. The results were evaluated with multivariate analyses. Pollen grains of Hyacinthella taxa are suboblate and oblate with 24.7–32.47 µm in the polar axis (P) to 29.72–41.5 µm in the equatorial diameter (E), and show reticulate-heterobrochate ornamentation. Pollen grains are monosulcate in all studied Hyacinthella taxa while incomplete zonosulcate in M. azureum. Although the pollen grains of the studied taxa of Hyacinthella are morphologically quite similar, the Cluster Analysis and Principal Component Analysis (PCA) demonstrate that the pollen size, sulcus length, sulcus width, murus thickness, pollen shape, and the lumen number and diameter are the most valuable characters, in the clustering of the studied Hyacinthella taxa. On the other hand, the aperture type was the most important characteristic in the separation of Hyacinthella taxa and Muscari azureum. Furthermore, the length of polar axis, sulcus length, sulcus width, lumen diameter and murus thickness were found significantly different among some species based on ANOVA test. The results indicate that pollen features can be used to separate some of the studied taxa.